Is the link between posttraumatic growth and anxious symptoms mediated by marital intimacy in breast cancer patients? - Canavarro, Maria Cristina (2015)
This study aimed to determine whether marital intimacy mediates the association between posttraumatic growth (PTG) and anxious symptoms in women who had recently completed breast cancer treatments and breast cancer survivors.